Вынесите общий множитель за скобки
y(a+c)+x(a+c)
x(3a+c)-z(3a+c)
a(b+c)+x(b+c)
a(3b+c)-x(3b+c)
Разложите на множители
xy3+5x2y2-3x2y
3a3b-6a2b2
2k(3k-4)+(3k-4)
a(b-c)+c(c-b)
2x(m-n)-(n-m)
7a4b3-14a2b4+21a2b3
(a+5) (a+5)-(a+3)(b+6)
(3x-1)(8b+1)+(7b-3)(1-3x)
a2b2-4ab3+6a3b
8x4y2-12x2y2
3y(2x-9)-5(2x-9)
k(x-y)+c(y-x)
3p(a-c)-(c-a)
3x5y2+15x4y3+12x5y4
(x+5)(2a+1)+(x+5)(3a-8)
(5m-3)(n+1)-(2n+3)(3-5m)
(3n+1)(3n-1)=(3n)² - 1²=9n² -1
ответ: В)
2)
(4x-1)²=(4x)² - 2*4x*1 +1²=16x² - 8x +1
ответ: Б)
3)
4a² - 25=(2a)² - 5²=(2a-5)(2a+5)
ответ: B)
4)
-0.09x⁴ + 81y¹⁶ = 81y¹⁶ - 0.09x⁴ = (9y⁸)² - (0.3x²)²=(9y⁸ - 0.3x²)(9y⁸+0.3x²)=
ответ: В)
5)
В) a² -4b²=(a-2b)(a+2b)
ответ: В)
6)
a² - 8a+16=(a-4)²
ответ: Б)
7)
ответ: Б)
8)
(x+8)(x-8)-x(x-6)=x² -64 - x² +6x=6x-64
ответ: Г)
9)
(7m-2)² - (7m-1)(7m+1)=49m² -28m+4 - 49m² +1= -28m+5
ответ: В)
10)
(c-4)² - (3-c)²=(c-4-3+c)(c-4+3-c)=-1(2c-7)= -2c+7=7-2c
ответ: Б)
11)
(x-4)² + 2(4+x)(4-x)+(x+4)² = (x-4)² -2(x+4)(x-4)+(x+4)²=
=(x-4-(x+4))²=(x-4-x-4)²=(-8)²=64
ответ: А)
12)
(4+a²)(a-2)(a+2)=(a²+4)(a²-4)=a⁴-16
ответ: Г)